2008
DOI: 10.1111/j.1600-0625.2007.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of synapse associated protein 102 expression in cyclosporin A‐stimulated hair growth

Abstract: Cyclosporin A (CsA) has been used as a potent immunosuppressive agent for inhibiting the graft rejection after organ transplantation. However, CsA provokes lots of side effects including hirsutism, the phenomenon of abnormal hair growth in the body. In the present study, we investigated the hair growth stimulating effect of CsA using in vivo and in vitro test models. When topically applied on the back skin of mice, CsA induced fast telogen to anagen transition. In contrast, CsA had no effect on the growth of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Hypertrichosis results when telogen or resting follicles are stimulated into anagen (active growth) or when nonpigmented vellus hair follicles are converted into longer, darker terminal hair follicles. Hypertrichosis can be congenital (hypertrichosis lanuginosa) or acquired (iatrogenic) from medications such as cyclosporine, steroids, penicillin, and streptomycin 3–5 . It can also occur as sequelae from underlying medical conditions, such as thyroid disease and porphyria 2 .…”
Section: History and Prevalencementioning
confidence: 99%
“…Hypertrichosis results when telogen or resting follicles are stimulated into anagen (active growth) or when nonpigmented vellus hair follicles are converted into longer, darker terminal hair follicles. Hypertrichosis can be congenital (hypertrichosis lanuginosa) or acquired (iatrogenic) from medications such as cyclosporine, steroids, penicillin, and streptomycin 3–5 . It can also occur as sequelae from underlying medical conditions, such as thyroid disease and porphyria 2 .…”
Section: History and Prevalencementioning
confidence: 99%
“…Despite its immunosuppressant activity, CsA provokes several side effects, such as nephrotoxicity, hypertension, and hirsutism (4,5). Among these side effects, the strong hairgrowth-stimulating activity of CsA has attracted significant attention from both the academic community and the cosmetics industry due to its great potential to treat alopecia (6,7). Mechanistically, it was revealed that CsA stimulates the growth of both murine hair epithelial cells and epidermal keratinocytes at an optimum concentration through inhibiting the expression and translocation of some protein kinase C isozymes that act as negative hair-growing factors (8).…”
mentioning
confidence: 99%
“…However, CsA provokes many side effects, including hirsutism, which is the phenomenon of abnormal hair growth on the body. In the present study, we investigated the stimulation of hair growth by CsA using hair epithelial cells [54]. Finally Shin et al reconstructed DP like tissues of DPCs and DSCs using a special medium and growth factors in vitro.…”
Section: Cell Culture Systemmentioning
confidence: 99%